Atorvastatin prevents amyloid-β peptide oligomer-induced synaptotoxicity and memory dysfunction in rats through a p38 MAPK-dependent pathway - Zhang, Ling-ling (Nature Publishing Group, 2014)
AIM: To investigate whether atorvastatin treatment could prevent Aβ(1-42) oligomer (AβO)-induced synaptotoxicity and memory dysfunction in rats, and to elucidate the mechanisms involved in the neuroprotective actions of atorvastatin. METHODS: SD rats were injected with AβOs (5 nmol, icv). The rats were administrated with atorvastatin (10 mg·kg(−1)·d(−1), po) for 2 consecutive weeks (the first dose was given 5 d before AβOs injection). The memory impairments were evaluated with Morris water maze task. The expression of inflammatory cytokines in the hippocampus was determined using ELISA assays. The levels of PSD-95 and p38MAPK proteins in rat hippocampus were evaluated using Western blot analysis. For in vitro experiments, cultured rat hippocampal neurons were treated with AβOs (50 nmol/L) for 48 h. The expression of MAP-2 and synaptophysin in the neurons was detected with immunofluorescence. RESULTS: The AβO-treated rats displayed severe memory impairments in Morris water maze tests, and markedly reduced levels of synaptic proteins synaptophysin and PSD-95, increased levels of inflammatory cytokines (IL-1β, IL-6 and TNF-α) and p38MAPK activation in the hippocampus. All these effects were prevented or substantially attenuated by atorvastatin administration. Pretreatment of cultured hippocampal neurons with atorvastatin (1 and 5 μmol/L) concentration-dependently attenuated the AβO-induced synaptotoxicity, including the loss of dendritic marker MAP-2, and synaptic proteins synaptophysin and PSD-95. Pretreatment of the cultured hippocampal neurons with the p38MAPK inhibitor SB203580 (5 μmol/L) blocked the AβO-induced loss of synaptophysin and PSD-95. CONCLUSION: Atorvastatin prevents AβO-induced synaptotoxicity and memory dysfunction through a p38MAPK-dependent pathway.